On a Methodological Approach of Notifying and Analysing Phrasemes in Epitaphs - Fabijanić, Ivo (Jezikoslovni zapiski, 2021)
This paper is about a novel methodological approach in identifying, notifying and analysing Croatian phrasemes in epitaphs. 138 phrasemes have been identified out of 127 epitaphs, from tombstones in the Pag communal graveyard. The analysis was based on a specific field research, the procedures, instruments and methodological framework, while the classification of phrasemes was based on Menac’s classification (2007): according to origin, form and style.